An Analysis of Content Validity on English Summative Assessment of Fifth Grade in The First Semester in Merdeka Curriculum - Ella Aprilia Tiana (Journal of English Teaching and Linguistic Issues (JETLI), 2024)
This paper was qualitative research and used content analysis design. This paper aims to analyze the content validity of English summative assessment and the writer tries to know whether the test items are in line with the learning objectives or not. It will describe the conformity and inconformity of three different English summative assessment from three different schools which already implemented Merdeka curriculum. The writer also tries to compare those three English summative assessments. The result showed that UPT SDN 51 Gresik has 100% valid items, UPT SDN 31 Gresik has 93% valid items, UPT SDN 16 Gresik has 91% valid items. Based on the criteria adopted from Arikunto’s opinion those three assessments have good items. It is better for the teacher before making a test looking at first in the flow of learning objective about the learning objective in every unit, so teacher can make test appropriate with the learning objective.